Education Professionals as Facilitators of Study Abroad Programs in Spain: Formal Training Needs - Amalia Herencia Grillo; Elena Hernández de la Torre (Universidad Nacional de Colombia, 2020)
This paper investigates an aspect of study abroad programs that has rarely been studied before: the training needs of local education professionals in Spain. Through a mixed-method, using a questionnaire completed by 103 participants, and interviews with 15 of them, we focus on their previous formal specific training and their perspective on the group of students they work with. Results show that most of them have rarely been trained on how to work as cultural facilitators for students from the US. This fact often creates a cultural gap and prevents the teachers from fulfilling their role as cultural bridges for students. Specific action needs to be taken in order to solve this lack of preparation in this group of professionals.